1999
DOI: 10.1074/jbc.274.34.24031
|View full text |Cite
|
Sign up to set email alerts
|

Cloning and Characterization of the Gene for a New Epithelial β-Defensin

Abstract: Mammalian ␤-defensins are endogenous cysteine-rich peptide antibiotics that are produced either by epithelial cells lining the respiratory, digestive, and urogenital tracts or by granulocytes and macrophages. A growing body of evidence has implicated these peptides in host defense, particularly mucosal innate immunity. We previously reported the cloning of the full-length cDNA for a porcine ␤-defensin (pBD-1), which was found to be expressed throughout the airway and oral mucosa. Here, we provide the structura… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
9
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(11 citation statements)
references
References 57 publications
2
9
0
Order By: Relevance
“…Zhang et al (8) and Elahi et al (33) previously showed pBD-1 to be constitutively expressed in different tissues (8). However, induction of pBD-1 mRNA expression may also be stimulated upon exposure to food contaminants or enteric pathogens (10,33,34) and is in line with our data, which show pBD-1 mRNA expression was upregulated following exposure to DON, NIV, ZEA, and FB1, individually and in mixtures. Elevated expression of pBD-1 in, for example, IECs may play a potential role in surveillance and maintenance of a homeostatic state of microflora on the mucosal epithelium and may be significant in preventing the development or progression of diseases (33,35,36).…”
Section: Discussionsupporting
confidence: 91%
“…Zhang et al (8) and Elahi et al (33) previously showed pBD-1 to be constitutively expressed in different tissues (8). However, induction of pBD-1 mRNA expression may also be stimulated upon exposure to food contaminants or enteric pathogens (10,33,34) and is in line with our data, which show pBD-1 mRNA expression was upregulated following exposure to DON, NIV, ZEA, and FB1, individually and in mixtures. Elevated expression of pBD-1 in, for example, IECs may play a potential role in surveillance and maintenance of a homeostatic state of microflora on the mucosal epithelium and may be significant in preventing the development or progression of diseases (33,35,36).…”
Section: Discussionsupporting
confidence: 91%
“…Gene-specific primers for pPGRP-L1 were sense, 5Ј-CTG TGG TAG CAG CAG CTT CTC TTT-3Ј, and antisense, 5Ј-GCT GCA GAA GCA ATC CAT ACA GGA-3Ј (cDNA nucleotides 12 to 35 and 256 to 233), and those for pPGRP-L2 were sense, 5Ј-AGC CCA GAG TTT CAA GGC CTG ATT-3Ј, and antisense, 5Ј-TCA GGA ACT GTG GCT CCA ATG TCT-3Ј (cDNA nucleotides 368 to 391 and 602 to 579). Primers for ␤-defensin-1 were as described previously (48). DNase-treated total RNA (500 ng) was used in each 25-l RT-PCR mixture.…”
mentioning
confidence: 99%
“…After amplification, 10 l of each reaction mixture was analyzed by 2% agarose gel electrophoresis, and bands were visualized by ethidium bromide staining. For Southern analysis, PCR products were transferred onto Hybond Nϩ filters (Amersham Pharmacia Biotech), hybridized with PGRP cDNA probes labeled with [␣-32 P]dCTP (3,000 Ci/mmol), and detected using autoradiography as previously described (48).…”
mentioning
confidence: 99%
“…Relatively little work have been done on porcine defensins and they have not yet been isolated from natural sources [7, 910]. pBD1, the first member of porcine β defensin, has a strong inhibitory activity against gram-negative bacteria [1112]. On the contrary, porcine β defensin 2 (pBD2) shows strong antibacterial activity against both gram-negative and gram-positive bacteria, including multi-resistant bacteria.…”
Section: Introductionmentioning
confidence: 99%